Optimal : how to sustain personal and organizational excellence every day - Goleman, Daniel (New York Harper Audio, 2024)
Optimal is the culmination of decades of scientific discoveries bearing on emotional intelligence. Enhanced emotional intelligence pays off in improved engagement, productivity, and more satisfying days. In this book, you'll find the keys to competence in emotional intelligence, and practical methods for applying this skill set more readily. It will equip you to become a highly effective leader and enable you to build an organizational culture that empowers workers to sustain high performance.
Keywords: Emotional intelligence. Organizational behavior